Phylogeography and Genetic Structure in the California Giant Salamander (Dicamptodon ensatus): Impacts of current and historic landscape features - Lavin, Brian R; Callahan, Briana S; Connell, Regan A; Girman, Derek J (Zootaxa, 2021)
The California Floristic Province contains numerous ecological regions and a complex geological and geographical history that make it one of the worlds biodiversity hotspots. A number of wide-ranging taxa span across these regions and show complex patterns of dispersal, vicariance and lineage diversification, making localized small ranged species with lower levels of vagility essential to understanding the overall region. Here, we investigate the biogeography and population structure of the California Giant Salamander (Dicamptodon ensatus) (Eschscholtz 1833), an endemic species localized to a narrow coastal region between two areas of biological significance in the California Floristic Province, the North Coast Divide and Monterey Bay. We sequenced one mtDNA fragment (control region) for 133 individuals and a subset of 38 individuals for the anonymous nuclear locus E16C7. We analyzed these sequences with phylogenetic, coalescent, Bayesian clustering, and population genetic approaches in order to infer population structure, phylogenetic structure, and biogeographic history. Additionally, we examined occurrence data with species distribution modeling to generate a habitat suitability map to aid our interpretation of geographic structure. Our analyses recovered 4 major mtDNA lineages, two of which are combined into 3 major lineages when nuDNA is examined. These 3 major lineages are bounded by 4 major current or past geological features; the North Coast Divide, the former Wilson Grove Embayment/current Petaluma Gap, San Francisco Bay, and Monterey Bay. Other low-vagility species linked to moist microclimates and forest habitat do share similarities with the genetic patterns of D. ensatus hinting at a larger role for the past Wilson Grove embayment and modern Petaluma Gap in California biogeography.